The politics of realism and social constructionism in psychology. (26th February 2020) - Ratner, Carl; Pavón‐Cuéllar, David; Ríos‐Martínez, Karla Montserrat
Abstract: This item presents a controversial discussion on the political implications of realist and social constructionist psychologies. After summarising a 2002–2005 debate between Kenneth Gergen and Carl Ratner on issues such as positivism, social constructionism and the political implications of psychological theories, it moves on to reproduce a discussion between Carl Ratner and David Pavón‐Cuéllar that took place in Morelia, Mexico in 2015. This discussion focuses on the contradiction between realism and social constructionism, and successively addresses subjective freedom, idealism and positivism, scientific objectivity, the truth claims and practical outcomes of psychological theories, the connection between science and politics, Gergen's attitudes toward other theories, social fragmentation as a consequence of social constructionism, technocracy, cultism, solipsism, the neutrality of science and its role in the Nazi regime, religion, and indigenous psychologies.